O transtorno do espectro do autismo e a educação física escolar: a prática do profissional da rede estadual de São Paulo - Quedas, Carolina Lourenço Reis (2015)
This study aimed to describe and analyze the experiences of physical education teachers on the inclusion of students with Autism Spectrum Disorder (ASD) in state schools in São Paulo, the eastern region. The field research was conducted specifically in the eastern region of São Paulo, and involved ten teachers. It adopted a qualitative and quantitative approach, carried out by the teacher's profile survey and semi-structured interviews. After the interviews were categorized and discussion of the collected data. The results showed the great difficulty that professionals have towards work with ASD student, is the lack of information, training, lack of support from school management and multidisciplinary discussion that directly affects the student - all these factors have been identified as hindering the teaching and learning. It was observed that there is exchange of experience between school staff and management team, and so there is no proper and adequate planning for students with ASD. The physical education professional, therefore, is no educational subsidies for the realization of their practice. The items that deserve attention by the Department of Education, Education Boards and schools and pointed in this research are significant for the abolition of existing attitudinal barriers between learning and teaching quality.